2019
DOI: 10.1186/s13104-019-4668-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting neonatal mortality in the general population: evidence from the 2016 Ethiopian Demographic and Health Survey (EDHS)—multilevel analysis

Abstract: Objective: This study was aimed to identify factors affecting neonatal mortality in Ethiopia. Results:According to the multilevel multivariable logistic regression analysis, the odds of neonatal mortality was significantly associated with husbands with no education (AOR = 2.30, 95% CI 1.10, 4.83), female birth (AOR = 0.57, 95% CI 0.39, 0.83), twin birth (AOR = 13.62, 95% CI 7.14, 25.99), pre-term birth (AOR = 15.07, 95% CI 7.80, 29.12) and mothers with no antenatal care (ANC) visit during pregnancy (AOR = 1.90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
52
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 28 publications
(38 reference statements)
17
52
0
6
Order By: Relevance
“…Similar ndings had been reported by other authors; Bello et al 32 reported a higher risk of death among out born preterm babies of lower gestation in Maiduguri, North Eastern Nigeria while Nga et al 18 identi ed poor referral system, place of birth and ethnicity as risk factors for neonatal deaths in rural north Vietnam. Over 75% of abdominal deliveries among our patients were performed presumably as a salvage procedure in most of the babies and this may account for the lower risk of mortality associated with C/S delivery.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar ndings had been reported by other authors; Bello et al 32 reported a higher risk of death among out born preterm babies of lower gestation in Maiduguri, North Eastern Nigeria while Nga et al 18 identi ed poor referral system, place of birth and ethnicity as risk factors for neonatal deaths in rural north Vietnam. Over 75% of abdominal deliveries among our patients were performed presumably as a salvage procedure in most of the babies and this may account for the lower risk of mortality associated with C/S delivery.…”
Section: Discussionsupporting
confidence: 87%
“…The focus of most community-based neonatal studies is the determination of sociodemographic risk factors for neonatal mortality. [15][16][17][18][19] On the other hand, hospital-based studies have the potential to identify speci c causes of neonatal mortality. [20][21][22][23] These two types of research studies complement each other in providing comprehensive data for holistic neonatal interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the response rate for the women's questionnaire in all years was very high (2004:97.6%, 2006:98.3, 2010:80%, 2014:95.7%). Finally, factors predicting neonatal survival in our analysis are congruent with previous findings [29,30,31].…”
Section: Discussionsupporting
confidence: 91%
“…wealth and education) [5,7]. Third, previous studies used traditional regression methods [8,10,11] that do not follow the WHO recommendation for inequality studies [9] or were limited to certain specific areas in the country without including the national context [11,12]. Finally, it assessed NMR inequality for the four Ethiopia Demographic and Health Surveys (EDHS 2000(EDHS , 2005(EDHS , 2011(EDHS , 2016 and was not limited to the first and the last EDHS rounds, unlike prior studies [5,13].…”
Section: Introductionmentioning
confidence: 99%